Dual emissive dinuclear Pt(ii) complexes and application to singlet oxygen generation. Issue 17 (20th April 2021) - Shafikov, Marsel Z.; Suleymanova, Alfiya F.; Kutta, Roger J.; Brandl, Fabian; Gorski, Aleksander; Czerwieniec, Rafał
Abstract : Dual emissive dinuclear Pt(ii ) complexes showing green fluorescence and infrared phosphorescence stemming from a single chromophoric moiety are reported. The compounds are efficient O2 photosensitizers with 1 O2 generation efficiencies of up to 77%. Abstract : Room-temperature dual emission consisting of spectrally separated fluorescence and phosphorescence is highly attractive as a design principle for ratiometric sensing materials, for example, for detection of dioxygen. Compounds susceptible to emission quenching by dioxygen, producing dioxygen in electronically excited states, are also used as photosensitizers for singlet oxygen generation. Combination of the dual emission behavior and efficient energy transfer from one of the emitting states (triplet state) of the dual emissive compound to molecular dioxygen can result in potent photosensitizers easily traceable by fluorescence spectroscopy, which may be advantageous for instance in biology studies. Herein, we present two Pt(ii ) complexes 1 and 2 of dinuclear structure which exhibit green fluorescence with sub-nanosecond lifetimes and near infrared (NIR) phosphorescence with microsecond lifetimes. Such properties are achieved via the design of a strongly π-excessive ditopic ligand with a N^C–C^N coordinating mode that bridges the metal centers. The ligand centered character of the lowest excited singlet (S1 ) and triplet (T1 ) states leads to strong exchange interaction of the unpaired electrons and hence to large energy separation Δ E (S1 –T1 ) amounting to 0.6 eV for 1 and 0.7 eV for 2, respectively. The large energy gap Δ E (S1 –T1 ) and weak metal contribution to the states S1 and T1 results in unusually long intersystem crossing (ISC) times τ ISC (S1 → T1 ) of 27.5 ps (1 ) and 65.2 ps (2 ), respectively, as determined by transient absorption spectroscopy. Owing to the slow ISC, the T1 → S0 phosphorescence of both 1 and 2 is accompanied by S1 → S0 fluorescence of comparable intensity. The large gap Δ E (S1 –T1 ) provides also a good optical separation of the two emissions. The phosphorescence signal is efficiently quenched in the presence of dioxygen, which is manifested in both the lower relative intensity and shorter decay time of phosphorescence. Thus, the compounds show high potential as ratiometric dioxygen sensing materials. The singlet oxygen photogeneration efficiencies of complexes 1 and 2, measured in air saturated dichloromethane, are as high as ϕ Δ ≈ 0.77 ± 0.1 and 0.57 ± 0.1, respectively. Thus, the compounds represent efficient singlet oxygen photosensitizers.